Evidence-Based Participatory Research Approaches for Last Mile Adolescent Girls and Young Women: A Reflection on the Study Methods - Lydia Kapiriri; Hanna Chidwick; Betty Kwagala; Deborah Mensah; David Owiredu; Lydia Osei (International Journal of Qualitative Methods)
There is increased interest in methods to achieve meaningful inclusion of traditionally marginalized and last mile populations in research. Adolescent girls and young women (AGYW) working in the artisanal small-scale mining (ASM) are an extremely marginalized group who, in addition to being excluded from decision making processes, tend to be excluded from research- even when the research is about them. There is a paucity of literature on the methods that can be used to meaningfully engage AGYW in ASM with limited education and knowledge in research. This paper provides a detailed description and reflection on a participatory, mixed-methods research process (involving a document review, survey, key informant interviews, focus group discussions and the nominal group technique) through which AGYW in ASM communities in Uganda and Ghana were involved to identify priority interventions to support their economic and health resilience. While the process, due to various challenges, took over 10 months to complete, it strengthened the AGYW’s capacity to meaningfully participate in the project and in decision making. Broad stakeholder engagement resulted in identifying relevant interventions whose implementation will improve the health and well-being of this last mile population. This paper highlights the contributions and challenges of using participatory research approaches among AGYW and other traditionally marginalized under researched populations to ensure that their voices are prioritized. Such participatory approaches are useful in ensuring that such last mile populations are not left behind on the path to achieving the 2030 Sustainable Development Goals.